PENGEMBANGAN ALAT PERAGA PEMBELAJARAN MATEMATIKA MATERI PERKALIAN BERBASIS MONTESSORI - Wahyudi, Apri; Choirudin, Choirudin (STIT Pringsewu, 2019)
Abstract This study aims to develop a learning tool to determine the results of multiplication of students to create a learning process that will be more interesting and fun. With the existence of Montessori teaching aids, this will improve the quality of the school and will be more advanced in the teaching and learning process. This study uses the Research and Development (R & D) method that produces a product, and tests the effectiveness of the product. From the results of the validation by material experts, media experts, mathematicians can be seen, the results of the validation of the material experts fall into the very feasible category. And screening trials by teachers and students fall into the category of proper use